Spontaneous outbreak of Astragalus pehuenches (Fabaceae) poisoning in cattle in Argentina - Martinez, Agustin (2018)
This is the first report of a spontaneous outbreak of Astragalus pehuenches poisoning on a farm in Argentine Patagonia, where 63 out of 70 cattle died. The main clinical signs of affected animals were ataxia, balance loss and progressive emaciation. Purkinje cells presented vacuolation and marginalization of the nucleus. Astragalus pehuenches was detected in the paddock as well as in the ruminal content and fecal matter samples of the affected animals. Swainsonine concentrations in Astragalus specimens were found to be as high as 0.096%.